A conceptual and semantic framework of the startup: A systematic review of the literature through a qualitative study - BOUHAJ , Said; JAHIDI , Rachid; LEBZAR , Bouchra (Revue Internationale du Chercheur, 2022)
This article aims to analyze the conceptual and semantic framework of the notion of startup. The results of our study come from a lexical and thematic processing of more than 274 definitions from scientific articles that were processed using Nvivo, a qualitative data analysis software made by QSR internationals. It appears that Anglophones authors share the definition by which the startup is an embryonic phase aiming to research and validate the business model. In contrast, in francophone research, the startup is a young innovative and technological company. Moreover, based on the plurality of semantic names attributed to the notion of a startup, this article aims to categorize startups according to several typologies. At the end of this work, we propose three major criteria to define the startup: the use of Lean Startup approaches (ALS) or agile methods, the research and validation of Innovation Business Model (IBM) and finally, the provisional character of the organization.